2006
DOI: 10.1021/jp0561874
|View full text |Cite
|
Sign up to set email alerts
|

A Small Paramagnetic Platinum Cluster in an NaY Zeolite:  Characterization and Hydrogen Adsorption and Desorption

Abstract: A well-defined cluster containing 12 equivalent platinum atoms was prepared by ion exchange of an NaY zeolite, followed by hydrogen reduction. It was characterized by electron paramagnetic resonance (EPR) spectroscopy, hyperfine sublevel correlation (HYSCORE), and theoretical calculations. Combing the results of the experiments with density functional calculations, the likely structure of this cluster is icosahedral Pt 13 H m , possibly with a low positive charge. The adsorbed H/D on the Pt cluster surface can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
94
3
15

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(123 citation statements)
references
References 70 publications
11
94
3
15
Order By: Relevance
“…The samples also give rise to an EPR spectrum that shows a multiplet due to a cluster of 12 equivalent Pt atoms with perhaps an invisible 13th atom [4]. The cluster size is compatible with the present EXAFS measurements, but this signal accounts for <1% of the total Pt in the sample.…”
Section: Fig 1 (Color Online) (A)supporting
confidence: 85%
See 4 more Smart Citations
“…The samples also give rise to an EPR spectrum that shows a multiplet due to a cluster of 12 equivalent Pt atoms with perhaps an invisible 13th atom [4]. The cluster size is compatible with the present EXAFS measurements, but this signal accounts for <1% of the total Pt in the sample.…”
Section: Fig 1 (Color Online) (A)supporting
confidence: 85%
“…It is the 5d band which is mainly engaged in bonds to chemisorbed molecules and when electrons are removed or added. Density functional calculations for Pt 13 found several distorted or even amorphous cluster geometries with energies lower by as much as 0.16 eV (1300 cm ÿ1 ) than those of an ideal icosahedron or cuboctahedron [3,8], also in the presence of chemisorbed hydrogen [4].The synthesis of small Pt clusters of 13-20 atoms in zeolite Y was reported previously [9], but there were no magnetic measurements. Here, Pt clusters were prepared in NaY zeolite by ion exchange with 3 mM aqueous Pt NH 3 4 Cl 2 solution, followed by stirring at 343 K for at least 48 h. Chemical analysis confirmed that this procedure leads to a Pt loading of ca.…”
mentioning
confidence: 80%
See 3 more Smart Citations